PTU-068 Biliary matrix metalloproteinase 9 levels are independent of neutrophil gelatinase-associated lipocalin in patients with malignant biliary obstruction. (28th May 2012) - Latif, A; Zabron, A; Horneffer-Van der Sluis, V; Wadsworth, C; Westaby, D; Vlavianos, P; Taylor-Robinson, S; Edwards, R; Khan, S
Abstract : Introduction: Better biomarkers are urgently needed to assist accurate diagnosis and appropriate treatment of malignant biliary obstruction, as, although malignancy is a common cause of obstructive jaundice, current diagnostic techniques often fail to differentiate benign from malignant disease. Molecular analysis of bile has recently produced promising candidate biomarkers. Previous work from our group found that biliary neutrophil gelatinase-associated lipocalin (NGAL), a small extracellular 25-kDa protein with several biological functions, differentiates obstructive jaundice from malignancy from that in benign disease. The mechanism of NGAL in hepatopancreatobiliary (HPB) malignancy is unknown, although in other systems it promotes neoplastic diffusion by complexing and stabilising matrix metalloproteinase-9 (MMP9), enabling local invasion. Aims: (1) To investigate possible biliary complexing of MMP9 and NGAL as a mechanism of tumorigenesis. (2) To validate our previous findings of biliary NGAL as a novel biomarker of malignancy in biliary obstruction. Methods: Bile samples were collected from 77 patients undergoing ERCP (n=77, 22 with malignant disease and 55 with benign disease) at Imperial College London. ELISA was used to quantify levels of MMP9/NGAL complexes and of NGAL and MMP9 occurring independently in bile. Pearson's correlation analysis was used to determine the relationship between NGAL, MMP9 and NGAL/MMP9 complex levels, and statistical significance assessed by the Mann–Whitney U test. Results: Biliary NGAL levels were significantly higher in malignant biliary obstruction compared to benign disease (median 1555 ng/ml vs 402 ng/ml, p=0.003), giving a ROC AUC of 0.74. Biliary MMP9 and NGAL/MMP9 complex levels were not different between these groups (p=0.527, p=0.760). Unbound biliary NGAL and MMP9 levels correlated poorly (r 2 =0.03, p>0.05). Unbound NGAL correlated poorly with complex (r 2 =0.07, p>0.05) whereas unbound MMP9 correlated with NGAL/MMP9 complex level (r 2 =0.73, p<0.05). Conclusion: This study is novel in confirming the presence of MMP9 in bile, alone and in complex with NGAL. However, although NGAL was increased in malignancy, MMP9 and MMP9/NGAL complex were not, suggesting that NGAL acts independently of MMP9 in endobiliary HPB malignancy. Mechanisms remain to be elucidated. This study also supports previous reports of NGAL as a novel and independent bile biomarker of malignant biliary obstruction. Competing interests: None declared.